Analysis of Short Term Financial Performance: A Case Study of an Energy Service Provider - Purba, Jan Horas Veryady; Septian, Muhammad Rayno (Universitas Syiah Kuala, 2019)
Objective This study aims to analyze the short-term financial performance of an energy service company, and compared to companies in the oil and gas mining sub-sector. The results of this study indicate the profit and loss, asset management, and profitability of the company in the last 5 years.Design/methodology The method used is descriptive method and quantitative method. The period of analysis of financial statement data is 2013-2017. This study uses (1) trend analysis to see a comprehensive picture of the company (2) financial ratio analysis to see company performance (3) comparative analysis comparing company financial statements with similar industries (4) SWOT analysis to determine strengths, weaknesses, opportunities, and threats and strategies needed by the company.Results The Cost of Goods per Sales ratio tends to decrease, so sales decline. The company's EBIT trends are relatively smaller than the industry average. This reflects that the sampled company has not maximized the company's EBIT. The company has tried to maximize gross profit and with good asset management will have an impact on increasing profitability in the future.